Why multilateral rules on competition are needed - Phedon Nicolaides (Intereconomics, 1994)
Even after the Uruguay Round overhaul, existing Gatt rules leave certain competition-distorting policies and practices unchecked. For various reasons the holes in the Gatt rules cannot be filled by the unilateral application of national competition regulations. It is therefore necessary to establish multilateral rules on competition.
Keywords: 330; International Trade